Contraception: historical development, current status and future aspects - Rabe, Thomas; Hartschuh, Elena; Runnebaum, Benno (Fertility control, 1999)
Since the birth of Christ, the world population has increased exponentially, although the real growth spurt only began in the early 19th century. The population increase in the so-called developing countries, e.g. Africa, India, China, accounts for 80% of the total population growth. Three children are born every second (98 million per year). By the year 2050, world population will have grown from a current 6 billion to 12.5 billion.
Gesehen am 20.11.2020